2004
DOI: 10.1016/s0002-9440(10)63292-0
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of CCR2 Ameliorates Progressive Fibrosis in Kidney

Abstract: Fibrosis is a hallmark of progressive organ diseases. Monocyte chemoattractant protein (MCP)-1, also termed as macrophage chemotactic and activating factor (MCAF/CCL2) and its receptor, CCR2 are presumed to contribute to progressive fibrosis. However, the therapeutic efficacy of MCP-1/CCR2 blockade in progressive fibrosis remains to be investigated. We hypothesized that blockade of CCR2 may lead to the improvement of fibrosis. To achieve this goal, we investigated renal interstitial fibrosis induced by a unila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
240
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(259 citation statements)
references
References 37 publications
(41 reference statements)
14
240
2
1
Order By: Relevance
“…1) because it has been previously reported that renal macrophages but not DCs mediate fibrosis in this model (16,18,66). However, Cx 3 cr1 GFP/GFP mice possessed similar or lower numbers of GFP + renal phagocytes under homeostatic conditions, in experimental glomerulonephritis and in kidney infection compared with CX 3 CR1-competent controls (3, 58), consistent with our present findings in UUO ( Fig.…”
Section: Cx3cr1 Deficiency Enhances Renal Fibrosissupporting
confidence: 91%
See 2 more Smart Citations
“…1) because it has been previously reported that renal macrophages but not DCs mediate fibrosis in this model (16,18,66). However, Cx 3 cr1 GFP/GFP mice possessed similar or lower numbers of GFP + renal phagocytes under homeostatic conditions, in experimental glomerulonephritis and in kidney infection compared with CX 3 CR1-competent controls (3, 58), consistent with our present findings in UUO ( Fig.…”
Section: Cx3cr1 Deficiency Enhances Renal Fibrosissupporting
confidence: 91%
“…In contrast, inappropriate macrophage functions promoted fibrosis in various organs (13,14). In the kidney, macrophages but not DCs mediated fibrosis in unilateral ureter ligation (UUO) and after ischemia/reperfusion (15)(16)(17)(18). Several mechanisms contribute to renal fibrosis, including the production of the main profibrotic molecule TGF-b (14,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the severity of interstitial fibrosis has been reported to determine the prognosis of kidney function [2]. To date, resident fibroblasts, epithelial-mesenchymal transition (EMT)-derived fibroblasts/myofibroblasts, and monocytes/macrophages have been suggested to be involved in the progression of kidney diseases [3,4]. However, the precise pathogenic mechanisms of tubulointerstitial lesions, especially related to interstitial fibrosis, in patients with CKD remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, cross-linking of myeloid IgA Fc receptors (Fc␣RI or CD89) aggravates IgA nephropathy and anti-GBM nephritis in an FcR␥-dependent manner (10). Macrophages and T cells are important in the inflammation associated with ureteral obstruction, another common cause of ESRD (11)(12)(13)(14)(15)(16). Conventional antiinflammatory therapy for ESRD, based on steroids, immunosuppressants, and angiotensin-converting enzyme inhibitors have limited efficacy on disease progression (17).…”
mentioning
confidence: 99%